A rapid method for pigeonpea wilt resistance screening - Y.L. NENE, M.P. HAWARE and (Indian Phytopathology, 2002)
A standardized rapid method for inoculating pigeonpea seedlings with Fusarium udum was developed to study host plant resistance under controlled conditions and to demonstrate the pathogenic variability in two Fusarium udum isolates.